[Cliffs Along Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of the cliffs along Heimaey. The tall, grass covered mountains sit along the grey beach and water ahead. A brown, jagged cliff covered sparsely in green grass is sat along the left edge of the photograph, surrounded by brown and orange rock along the water. White fumes are visible in the background to the right of the cliff in the foreground. Three pillar-like rock formations sit along the dark beach at the center of the photograph. The sky is covered in grey clouds.